(untitled) (Journal of Medicine, 2025)
Background: Dengue fever is a painful febrile illness caused by a mosquito-borne Arbovirus. Epidemic episodes often occur during the rainy season. Complete blood count (CBC) is essential in patients with dengue fever and serological tests are necessary to confirm it. This study aimed to evaluate the hematological changes in dengue fever patients in Jashore Medical College Hospital, Bangladesh. Methods: This prospective cross-sectional study was conducted in the Department of Medicine, Jashore Medical college Hospital, Bangladesh from July 2023 to Decembar 2023. The study involved 177 dengue fever patients identified through NS1 and/or IgM antibody tests. Purposive sampling was used for patient selection, and data analysis utilized SPSS version 23.0. Results: Analysis of hematological parameters on the 1st and 3rd days indicated significant shifts in platelet, leucocyte, neutrophil, and lymphocyte counts. Platelet count decreased from 99.67±96.17 x 109/L to 82.72±60.84 x 109/L (p=0.048). Leucocyte count rose from 6.43±3.01 x 109/L to 7.85±5.58 x 109/L (p=0.003), while neutrophil count decreased from 6.31±1.38 x 109/L to 5.44±1.36 x 109/L (p<0.001). Lymphocyte count also increased from 3.06±1.80 x 109/L to 3.78±1.19 x 109/L (p<0.001). No significant shifts were observed in hemoglobin (p=0.579) or hematocrit (p=0.639) levels. Conclusion: Among dengue fever patients, platelet and neutrophil counts decrease while leukocyte and lymphocyte counts increase significantly between the 1st and 3rd days. However, there are no significant shifts observed in hemoglobin or hematocrit levels in the same tenure. J MEDICINE 2025; 26: 43-47